PENGARUH AUDIT COMPLIANCE (AUDIT KEPATUHAN) TERHADAP EFEKTIVITAS PELAYANAN DI BASARNAS PROVINSI BENGKULU - syafrudin AB (Jurnal Ilmu Akuntansi, 2020)
The purpose of this study was to determine the effect of audit compliance (audit compilance) on the effectiveness of services in BASARNAS Bengkulu. Based on the results of the study it is known that there is an influence between audit compliance with service effectiveness with a Fcount value of 869,195 greater than Ftable with a significance level of 0,000 <0.05, which means audit compliance provides a positive influence on service effectiveness. The more compliant the BASARNAS team in carrying out its SOPs, the more effective the services provided. The t-test value for the audit compliance variable (X) obtained by t-test is greater than t table, which is 2.986> 1.677 and the significance value is 0.003 <0.05 which means that the audit compliance variable has a positive and significant effect on the effectiveness of the service (Y) partially.